Self-instructional teaching module based on cognitive load theory - Ong, Chiek Pin (2008)
Basically an instructional computer module consists of two media namely text and visuals. These multiple representations can complement each other, resulting in a more complete representation of an application domain than a single source of information does. According to cognitive load theory, instruction needs to be designed in a manner that facilitates the acquisition of knowledge in long-term memory while reducing unnecessary demands on the working memory. Presenting information in a way that cognitive load falls within the limitations of working memory can improve speed and accuracy of understanding, and facilitate deep understanding of information content. The aim of this study is to produce a self-instructional teaching module based on Cognitive Load Theory with principles of minimalism in an attempt for easier and faster learning and comprehension among teacher trainees. The module will be compared to the conventional instruction in terms of achievements based on the time of response and information retention. It is expected that the results would reveal that the cognitively guided module which physically integrate text and visuals would show to be far superior a learning tool than the conventional computer module instruction.